2007
DOI: 10.1590/s0100-54052007000400004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização molecular e patogênica de isolados de Xanthomonas albilineans (Ashby) Dowson, agente causal da escaldadura das folhas da cana-de-açúcar

Abstract: Leaf scald is among the five more important diseases in sugarcane and its occurrence reduces yield and crop longevity. Resistant cultivars have been used to control the disease, but there is evidences of the occurrence of variants of the pathogen. In commercial fields located in São Paulo State, it has been observed that one sugarcane cultivar can show symptoms in some regions but not in anothers, suggesting the presence of variants within the pathogen population. Thus, the aim of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…hybrid groups, indicating that host isolation might be the main driving force causing the genetic differentiation of the Xa population in China, particularly for the Xa strains hosted in the local cultivar (Taoshangguozhe), in the city of Ruian in Zhejiang province. A previous study suggested that bacteria variants and the reaction of sugarcane cultivars contributed to the genetic and aggressive diversity within the Xa population in the state of São Paulo in Brazil [ 34 ]. The interaction between pathogens and specific hosts can cause genetic differentiation of pathogen populations, which is related to the resistance levels of different hosts [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…hybrid groups, indicating that host isolation might be the main driving force causing the genetic differentiation of the Xa population in China, particularly for the Xa strains hosted in the local cultivar (Taoshangguozhe), in the city of Ruian in Zhejiang province. A previous study suggested that bacteria variants and the reaction of sugarcane cultivars contributed to the genetic and aggressive diversity within the Xa population in the state of São Paulo in Brazil [ 34 ]. The interaction between pathogens and specific hosts can cause genetic differentiation of pathogen populations, which is related to the resistance levels of different hosts [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eor instance, the genetic diversity of 50 isolates of X. albilineans from commercial areas of the state of Sao Paulo, Brazil was assessed by rep-PCR (41) and grouped the isolates into three groups. Eor instance, the genetic diversity of 50 isolates of X. albilineans from commercial areas of the state of Sao Paulo, Brazil was assessed by rep-PCR (41) and grouped the isolates into three groups.…”
Section: Discussionmentioning
confidence: 99%
“…As alterações implicam na redução da dependência por produtos químicos e outros insumos energéticos e o maior uso de processos biológicos nos sistemas agrícolas (BETTIOL; GHINI, 2003 A exploração da atividade biológica de metabólitos secundários presentes no extrato bruto ou óleo essencial de plantas medicinais pode se constituir, ao lado da indução de resistência, em uma forma potencial de controle alternativo de doenças de plantas cultivadas, como o confirmado por Zacaroni et al (2009) Tais estudos suplementam a relevância de pesquisas descrita por Silva (2005), em que a bactéria Xanthomonas albilineans, patógeno de uma das principais doenças dos cultivares de cana-de-açúcar, a escaldadura das folhas, é apontado como causador de perdas significativas na produção.…”
Section: Cadernos Unifoaunclassified